The Energetic People Development Center (EPDC) Role in Improving Public Speaking Participants Ability Program - Dewi Eldianti; Halomoan Harahap (Journal of Multidisciplinary Academic, 2021)
This study focuses on examining the role of the EPDC (The Energetic People Development Centre) program in improving the skills of public speaking participants. The objectives of this study are 1) To describe the role of the EPDC program in EPDC participants; 2) To describe the constraints of the program. This research uses a case study research method. For this research, the object of research is the role of the EPDC. While the subjects of this study were participants of the EPDC (The Energetic People Department Centre). Data collection techniques using interviews. The validity of the research data used data triangulation and source triangulation. After obtaining the data obtained, the results of the study indicate that with a tutor, character, and behaviour turned out to support the success of public speaking skills. The conclusion is the ability of public speaking participants after attending the training given progress.